The impact of airwave on tangential and normal components of electric field in seabed logging data - Rostami, A. (American Institute of Physics Inc., 2016)
Seabed Logging (SBL), is a recently used application of Controlled Source Electromagnetic (CSEM) method based on study on resistivity of layers beneath seafloor, to delineate marine hydrocarbon reservoir. In this method, an ultra-low frequency electromagnetic (EM) wave is emitted by an electric straight dipole which moves parallel to the seabed. Following Maxwell's equations, reflected and refracted waves from different layers are recorded by receiver line which is laying on the sea floor to define the contrast between amplitude and phase of responding waves of bearing oil reservoir and surrounding host rocks. The main concern of the current work is to study behavior of airwave, which is propagated wave in the seawater area, guided by sea surface and refracted back to the receiver line, and its impact on tangential and normal components of received electric field amplitude. Will be reported that the most significant part of tangential component is airwave, while it does not affect normal component of received electric field, remarkably. Â© 2016 Author(s).